Effect of Economic Growth and Inflation on Minimum Wages in Badung District Bali Province - Murthi, Ngurah Wisnu (Social Science Academic, 2023)
Many factors can influence the minimum wage in Badung Regency, namely economic growth and the rate of inflation that occurs. The aim of this research is to determine the effect of economic growth and inflation rate on minimum wages in Badung Regency, Bali Province, both partially and simultaneously. Data analysis was carried out using the multiple linear regression method. Based on data analysis, the results obtained are (1) economic growth has a positive and real partial effect on the minimum wage in Badung Regency, Bali Province, 2) the inflation rate has an effect partially positive and real on the minimum wage in Badung Regency, Bali Province, (3) economic growth and the inflation rate simultaneously have a real effect on the minimum wage in the Regency Badung, Bali Province. To the Tabanan Regency government, considering that the issue of wages is a very important problem, it is hoped that the Badung Regency government will pay more attention to these two variables in order to increase the minimum wage for Badung Regency